`int(3\ dx)/(xsqrt(4-x^2))`

This contains a `sqrt(a^2-x^2)` term, so we will use a substitution of `x =a\ sin\ theta`.

So `a=2`, and we let `x = 2\ sin\ θ`, so `dx = 2\ cos\ θ\ dθ`.

Substituting and simplifying the square root gives:

`sqrt(4-x^2)=sqrt(4-4 sin^2 theta)`

`=sqrt(4(1-sin^2 theta))`

`=2sqrt(cos^2 theta)`

`=2\ cos\ theta`

Substituting everything into the integral gives:

`int(3 dx)/(xsqrt(4-x^2))=int(3(2\ cos\ theta\ d theta))/((2\ sin\ theta)(2\ cos\ theta))`

`=3/2int(d theta)/(sin\ theta)`

`=3/2intcsc\ theta\ d theta`

`=3/2ln\ |csc\ theta-cot\ theta|+K`

`=3/2ln\ |2/x-(sqrt(4-x^2))/x|+K`